2022
DOI: 10.3390/su14042397
|View full text |Cite
|
Sign up to set email alerts
|

An Employee Competency Framework in a Welfare Organization

Abstract: Purpose—The aims of the current study were as follows: (1) to develop a framework of the job competence of employees to examine the recruitment of employees in their specialized fields, and (2) to answer the question of whether the development of that framework of the job competence of employees in attracting and employing people or their appointment and promotion was effective in achieving the goals of the organization. Design/methodology—Researchers examined the work environment of a branch of the Welfare Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The fundamental and core of corporate culture construction lies in refining a set of spiritual concepts that align with the reality of the enterprise, and mission, vision and values are the focus of corporate culture construction [9]. The study found a correlation between individual organizational behavior of organizational culture and employees who have collectivist values being more inclined to adopt organizational behavior.…”
Section: Corporate Strength Productmentioning
confidence: 87%
See 1 more Smart Citation
“…The fundamental and core of corporate culture construction lies in refining a set of spiritual concepts that align with the reality of the enterprise, and mission, vision and values are the focus of corporate culture construction [9]. The study found a correlation between individual organizational behavior of organizational culture and employees who have collectivist values being more inclined to adopt organizational behavior.…”
Section: Corporate Strength Productmentioning
confidence: 87%
“…Figure 3. Method of analyzing organizational and individual behaviors of employees and their behavior motivationsSource: developed by the author based on[9] …”
mentioning
confidence: 99%